Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan - Rahmad Bahagia; Linzzy Pratami Putri (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This research is motivated by the dissatisfaction experienced by some employees in work caused by lack of communication and concern of superiors in work operations and in employee career development. Another thing that causes employee dissatisfaction is the uncomfortable work environment for employees. This type of research is associative research and samples were taken as many as 104 people. The data collection techniques in this study list questions (Questioners). The data used is quantitative data and in analysis using classic assumption data analysis techniques, multiple linear regressions and hypothesis testing. Based on the results of the study, partial communication has a significant influence on employee job satisfaction, career development has a significant effect on employee job satisfaction and the work environment also has a significant influence on employee job satisfaction. Simultaneously the influence of communication, career development and work environment on employee job satisfaction is obtained gis value. (2 tailed) amounting to 0.000 < ?0.05 it can be stated that communication, career development and work environment significantly affect the job satisfaction of employees of PT employees. PLN (Persero) Medan Area.